Direct regeneration of shoot from axillary bud of Citrus reticulate - Shende, C. B.; Manik, S. R. (International Journal of Agricultural Technology, 2015)
Young axillary buds of mature plant of Citrus reticulata were cultured on MS medium (1992) containing 6-Benzyl amino purine (BAP) 0.25, 0.50,1.00,1.50 & 2.00 mg/l. The best results for multiple shoots were obtained with 1.50 mg/l. The highest degree of Callus was induced on BAP 1.00 mg/l plus NAA 0.25 mg/l. The transfer of multiple shoots on rooting medium containing NAA 0.25 mg/l induced good rooting.